The key molecular pattern BxCDP1 of Bursaphelenchus xylophilus induces plant immunity and enhances plant defense response via two small peptide regions - Hu, Long-Jiao; Wu, Xiao-Qin; Wen, Tong-Yue; Ye, Jian-Ren; Qiu, Yi-Jun; Rui, Lin; Zhang, Yan (Frontiers in Plant Science, 2022)
The migratory plant-parasitic nematode Bursaphelenchus xylophilus is the pathogen of the pine wilt disease (PWD), causing serious damages to pine forests in China. During the process of plant resistance to multiple pathogens, the plant immunity plays a key role. In this current study, the pathogen-associated molecular pattern (PAMP) BxCDP1 in B. xylophilus has been identified, but host target protein of BxCDP1 and its key amino acid region inducing the plant immunity have yet to be elucidated. We found that BxCDP1 could trigger superoxide and H2O2 production, and callose deposits. A RING-H2 finger protein 1 (RHF1) of Pinus thunbergii was screened and characterized as a target protein of BxCDP1 by yeast two-hybrid and Co-Immunoprecipitation (Co-IP). Moreover, two peptides (namely M9 and M16) proved to be key regions of BxCDP1 to induce PAMP-triggered immunity (PTI) in Nicotiana benthamiana, which also induced the expression of pathogenesis-related (PR) genes (PtPR-3, PtPR-4, and PtPR-5) in P. thunbergii and enhanced the resistance of host to B. xylophilus. These results indicate that BxCDP1 plays a critical role in the interaction between B. xylophilus and P. thunbergii, and both peptides M9 and M16 have potentials to be developed and utilized as immune inducers of pines against B. xylophilus in the future.